(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Liinc em Revista Vol. 8, n. 2 (2012) Link de acesso ao número http://revista.ibict.br/liinc/index.php/liinc/issue/view/40